2022
DOI: 10.3390/ijms232314796
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Interactions Are the Primary Determinant of the Binding Affinity of SARS-CoV-2 Spike RBD to ACE2: A Computational Case Study of Omicron Variants

Abstract: To explore the mechanistic origin that determines the binding affinity of SARS-CoV-2 spike receptor binding domain (RBD) to human angiotensin converting enzyme 2 (ACE2), we constructed the homology models of RBD-ACE2 complexes of four Omicron subvariants (BA.1, BA.2, BA.3 and BA.4/5), and compared them with wild type complex (RBDWT-ACE2) in terms of various structural dynamic properties by molecular dynamics (MD) simulations and binding free energy (BFE) calculations. The results of MD simulations suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 70 publications
1
19
0
Order By: Relevance
“…Therefore, the strong electrostatic repulsion between Sb16 and E484K decreases the binding affinity, highlighting the essential role of electrostatic interactions in protein binding. [46][47][48][49] Our results agree with the experimental finding that the E484K mutation prevents Sb16 from binding to it. 22 From Table 6, it can be seen that the K417N mutation has no significant impact on the binding affinity to Sb16.…”
Section: Residuessupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, the strong electrostatic repulsion between Sb16 and E484K decreases the binding affinity, highlighting the essential role of electrostatic interactions in protein binding. [46][47][48][49] Our results agree with the experimental finding that the E484K mutation prevents Sb16 from binding to it. 22 From Table 6, it can be seen that the K417N mutation has no significant impact on the binding affinity to Sb16.…”
Section: Residuessupporting
confidence: 89%
“…Recent theoretical studies have emphasized that electrostatic interactions play a primary role in determining the binding affinity between SARS-CoV-2 RBD and human ACE2. 15,46 Silva et al 47 suggested that the electrostatic interactions could serve as a robust descriptor for rapid screening of the RBD-antibody binding affinity, and they identified electrostatic epitopes on the SARS-CoV-1 and SARS-CoV-2 RBD proteins for four effective antibodies and ACE2. As seen in Table 3, the difference in binding affinity should be mainly attributed to the electrostatic interactions between RBD and nanobodies.…”
Section: Comparative Study Of the Binding Of Rbd To Sb16 And Sb45mentioning
confidence: 99%
“…The binding affinity between angiotensin-converting enzyme 2 (ACE2) receptor and receptor-binding domain (RBD) is primarily driven by multiple intermolecular forces, including hydrogen bonding, electrostatic interactions, van der Waals forces, and salt bridges. The hydrogen-bonding network at the binding interface between wild-type ACE2 and RBD consisted of an average of nine hydrogen bonds, which contributed significantly to the stability of the complex (Figure S9a). However, upon analysis of the mutations, excluding the omicron variant, the hydrogen-bonding network was reduced to an average of seven hydrogen bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Due to its critical function in the immune response and defense against pathogen infections, STAT1 is typically thought of as a tumor suppressor [ 22 ]. However, a number of illnesses, including Acne vulgaris , have been linked to aberrant STAT1 activity [ 23 ]. Although there has been progress in our understanding of STAT activation, little is known about how STAT signals are downregulated, which is consistent with our recommended therapeutic approaches [ 24 ].…”
Section: Discussionmentioning
confidence: 99%